Development of Physics 1 online module using Maasive Open Online Course (MOOC) - NORBAIZURA NORDIN; HARSHINY A/P NALLIAH; WAN NUR AISHAH MAULAT WAN SUBHE; NUR AIMA HUSNA BINTI ISMAIL (Journal of Advanced Research in Social Sciences and Humanities, 2019)
Aim: This research aimed to better understand first-year Physics instructors and their students’ challenges at University Tun Hussein Onn Malaysia (UTHM).Method: The ADDIE Model was a guiding principle for the duration of this project’s development and completion. The problem has been identified, which will aid in creating a MOOC online module to address it. A quiz is included at the end of each chapter of the online module to ensure that students have fully grasped the material covered there. Additionally, a second questionnaire was given out to 60 diploma students to gauge their opinion of the developed online module.Findings: The positive responses to the second survey indicate that the online module has improved students’ grasp of the fundamentals of Physics 1. This Physics 1 online module should be adapted into a novel application, like a compact disc, so students can use it without an internet connection.Implications/Novel Contribution: Because of this online module, professors can spend less time on theoretical explanations and more time on interactive exercises, allowing their students to gain a deeper grasp of the material covered in class.